Computing travel impendences using trip generation regression model: a phenomenon of travel decision-making process of rural households - Talpur, M.A.H. (Springer Science and Business Media B.V., 2022)
The travel accessibility problems resulted from the lack of transportation facilities and socioeconomic opportunities. These are often called travel impedances. At remote locations, the travel impedances severely affect the decision-making processes of households to satisfy basic needs. Thus, this study aims to highlight the impedance factors of rural households, using the trip generation regression model as an optimum accessibility measure. The study area was selected as Badin, the deprived subregion of southern Pakistan. Pakistan is the 5th most populous country in the world recently beating Brazil. More than 60 of Pakistanâs total population is living in rural areas without essential transportation services. The truancy of a rural transport policy can be said as one of the reasons behind the vulnerability of rural Pakistan. Hence, the householdâs trip purposes were anticipated to the income, size, distance, and travel time. With the help of cluster sampling, the questionnaire survey was performed from a random sample of 100 households. The model, regional household trips by purpose (RTp), revealed strong-positive correlation values of R = 0.998 and R2 = 0.997. The larger household size and lower household income were found as acute impedances compared to travel time and distance. In other words, the higher population size and lack of economic opportunities were reported as the main findings of this study. This research deliberated the concept of a trip generation that is rarely executed to underline impedances of rural households. The study's findings can assist transport planners to formulate policy proposals for not only rural subregions but also urban centers of developing and developed countries. Â© 2022, The Author(s), under exclusive licence to Springer Nature B.V.